Towards objective metrics for blind assessment of images quality - Brandão, T.; Queluz, P. (2006 IEEE International Conference on Image Processing, ICIP 2006, 2006)
This paper describes a watermark-based technique that scores the quality of an image by blind estimation of its PSNR. Watermark embedding is performed in the block-based DCT domain using a non-uniform quantization scheme that accounts for human vision characteristics. At the extraction, the square distances between received coefficients and nearest quantization points are computed, giving an estimative for the image mean square error (and consequently, its PSNR). Since these distances may be underestimated if distortion is greater than the quantization step used for watermark embedding, it is also proposed the use of watermark extraction bit error rate (together with image statistics) as means of PSNR estimation weighting. Results show that PSNR estimation closely follows the true PSNR, for images subject to JPEG and JPEG2000 compression.